Religious Moderation from the Perspective of KMA 450 - Siti Ropiah; Muhamad Abduh (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to analyze the implementation of religious moderation based on the Regulation of the Minister of Religious Affairs (KMA) No. 450 in Indonesia, particularly in education and religious life. KMA No. 450 emphasizes the importance of applying the principles of moderation, such as balance, tolerance, justice, and respect for diversity, as an effort to foster harmony in a plural society. Religious moderation not only serves as a foundation in religious education curricula but also as a guideline in social interactions. The research employs a qualitative descriptive approach by examining the document of KMA No. 450 and its supporting policies. The findings reveal that KMA No. 450 has a positive impact on shaping moderate attitudes among students and the community. The values of religious moderation taught through Islamic religious education help prevent intolerance and extremism while nurturing awareness of the importance of coexisting in diversity. However, its implementation faces challenges, such as resistance from certain groups and limited resources. The study recommends enhancing the dissemination of moderation values, providing training for educators, and developing curricula and teaching materials based on religious moderation. With proper implementation, KMA No. 450 has the potential to serve as a strategic guide in fostering peaceful and harmonious religious life in Indonesia.